Factors associated with high compliance behaviour against COVID-19 in the early phase of pandemic: a cross-sectional study in 12 Asian countries. Issue 8 (9th August 2021) - Chua, Chun En; Kew, Guan Sen; Demutska, Alla; Quek, Sabrina; Loo, Evelyn Xiu Ling; Gui, Hao; Wong, Scott; Lau, Hui Xing; Low, En Xian Sarah; Loh, Tze Liang; Ooi, Shien Lung; Hung, Emily C W; et al.
Abstract : Introduction: Regardless of having effective vaccines against COVID-19, containment measures such as enhanced physical distancing and good practice of personal hygiene remain the mainstay of controlling the COVID-19 pandemic. Countries across Asia have imposed these containment measures to varying extents. However, residents in different countries would have a differing degree of compliance to these containment measures potentially due to differences in the level of awareness and motivation in the early phase of pandemic. Objectives: In our study, we aimed to describe and correlate the level of knowledge and attitude with the level of compliance with personal hygiene and physical distancing practices among Asian countries in the early phase of pandemic. Methods: A multinational cross-sectional study was carried out using electronic surveys between May and June 2020 across 14 geographical areas. Subjects aged 21 years and above were invited to participate through social media, word of mouth and electronic mail. Results: Among the 2574 responses obtained, 762 (29.6%) participants were from East Asia and 1812 (70.4%) were from Southeast Asia (SEA). A greater proportion of participants from SEA will practise physical distancing as long as it takes (72.8% vs 60.6%). Having safe distancing practices such as standing more than 1 or 2 m apart (AdjOR 5.09 95% CI (1.08 to 24.01)) or more than 3 or 4 m apart (AdjOR 7.05 95% CI (1.32 to 37.67)), wearing a mask when they had influenza-like symptoms before the COVID-19 pandemic, preferring online news channels such as online news websites/applications (AdjOR 1.73 95% CI (1.21 to 2.49)) and social media (AdjOR 1.68 95% CI (1.13 to 2.50) as sources of obtaining information about COVID-19 and high psychological well-being (AdjOR 1.39 95% CI (1.04 to 1.87)) were independent factors associated with high compliance. Conclusions: We found factors associated with high compliance behaviour against COVID-19 in the early phase of pandemic and it will be useful to consider them in risk assessment, communication and pandemic preparedness.